Angels walking - Kingsbury, Karen (New York : Howard Books, a division of Simon & Schuster, Inc., 2014)
After suffering a career-ending injury, Tyler Ames finds a maintenance job at a retirement home where he meets Virginia Hutcheson, a patient with Alzheimer's who seems to have the answers he is seeking.
Includes a reading group guide.
Keywords: Janitors -- Fiction; Alzheimer's disease -- Patients -- Fiction; Miracles -- Fiction; Christian fiction